RUSSIAN MEANS OF EXPRESSION OF MOTIVATION IN THE MODERN RUSSIAN LANGUAGE - Sayyora Dadaxanova (Web of Journals Publishing, 2025)
This article examines the means of expression of motivation in the modern Russian language. Various grammatical, lexical and stylistic constructions used to convey motivational meanings are analyzed. Special attention is paid to the comparison of traditional and modern ways of expressing motivation, as well as their functioning in different communicative situations.
Keywords: Motivation, modern Russian language, grammatical constructions, lexical means, stylistic technique.